2014
DOI: 10.1038/ni.2794
|View full text |Cite|
|
Sign up to set email alerts
|

STAT1-cooperative DNA binding distinguishes type 1 from type 2 interferon signaling

Abstract: STAT1 is an indispensable component of a heterotrimer (ISGF3) and a STAT1 homodimer (GAF) that function as transcription regulators in type 1 and type 2 interferon signaling, respectively. To investigate the importance of STAT1-cooperative DNA binding, we generated gene-targeted mice expressing cooperativity-deficient STAT1 with alanine substituted for Phe77. Neither ISGF3 nor GAF bound DNA cooperatively in the STAT1F77A mouse strain, but type 1 and type 2 interferon responses were affected differently. Type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 50 publications
3
72
1
2
Order By: Relevance
“…The ability of STAT1␤ to induce Irf1 may account for ISRE-regulated gene induction during secondary responses. It is unclear how STAT1␤ induces Irf1, but the mechanism may involve a recently identified ISRE around 7 kb upstream of the transcription start site of the Irf1 gene (66). However, STAT1␤ is not able to perform all the functions of STAT1␣, and our data reveal that over 16% and 9% of genes are induced only by STAT1␣.…”
Section: Time After Treatment Ti Ti Ti Ft Ft Ft T T T T T T T T Tmentioning
confidence: 66%
“…The ability of STAT1␤ to induce Irf1 may account for ISRE-regulated gene induction during secondary responses. It is unclear how STAT1␤ induces Irf1, but the mechanism may involve a recently identified ISRE around 7 kb upstream of the transcription start site of the Irf1 gene (66). However, STAT1␤ is not able to perform all the functions of STAT1␣, and our data reveal that over 16% and 9% of genes are induced only by STAT1␣.…”
Section: Time After Treatment Ti Ti Ti Ft Ft Ft T T T T T T T T Tmentioning
confidence: 66%
“…55 Distinct type I and II IFNs are used in different contexts for hematopoietic development. 56,57 Previous work in zebrafish and mice suggest that IFN-g promotes HSC emergence in midgestation embryos but zebrafish lack an IFN-a homolog, thus leaving the role of this type I IFN unexplored. 16,18 Whereas IFN-g promotes HSC emergence, our data argue that IFN-a promotes partial AGM HSC maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in response to IFN-a, STAT2 was shown to form, independently from STAT1, a complex with IRF9 (28) that binds ISRE and mediates ISG expression (29). Also, it was shown that whereas STAT1 cooperativity is essential for IFN-g response, it is dispensable for IFN-a signaling (30). Very recently, it has been reported that IFN-a activates the STAT2/IRF9 complex that forms an ISGF3-like response without STAT1 and generates an antiviral response in the absence of STAT1 (31).…”
Section: Discussionmentioning
confidence: 99%
“…5E). In this experiment, we observed two different levels of inhibition: one intermediate, between 30 and 50% (gray), and a nearly complete inhibition of ∼80-90% (black). These two phenotypes illustrate the dual effect of SUMO paralogs on IFN-g signaling, by acting both on STAT1 phosphorylation and PML stability.…”
Section: Sumo1 or Sumo3 Expression Reduces Ifn-g But Not Ifn-a Transcmentioning
confidence: 99%